Runoff Coefficient in the Air Bengkulu Watershed and the Evaluation of the Existing Spatial Planning - Sulistyo, Bambang; Adiprasetyo, Teguh; Murcitro, Bambang Gonggo; Purwadi, Agus Joko; Listyaningrum, Noviyanti (Faculty of Geography, Universitas Gadjah Mada, 2024)
Runoff coefficient plays a crucial role in estimating the peak discharge of a river basin. Therefore, this research aimed to investigate runoff coefficient in the Air Bengkulu watershed based on temporal land cover data and evaluate the existing spatial planning. Land cover data from 1998, 2002, 2016, and 2023, with spatial patterns derived from current regional planning were used. The temporal and spatial pattern-based runoff coefficients were determined using land cover data and spatial pattern function, respectively. Meanwhile, descriptive and comparative methods were adopted based on time. The calculated runoff coefficient was 0.073, 0.093, 0.276, and 0.273 for 1998, 2002, 2016, and 2023, while the value obtained based on spatial patterns was 0.306. Additionally, a general trend of increasing the values over time was observed. Land cover change, particularly the decline of forest areas and the expansion of settlement and plantation, contributed to the rising runoff coefficient. The results showed that runoff coefficient (0.306) exceeded the current land cover, similar to other analyses with higher runoff in the predicted scenario. This research suggested a need for a more detailed classification system and scale to accommodate land cover types with relatively low runoff coefficient. In risk assessment, land cover-like spatial patterns with low runoff coefficient should be placed as capacity other than vulnerability components.